Damping modification factors for SDOF systems subjected to near-fault, far-fault and artificial earthquakes. - Hatzigeorgiou, George D. (Earthquake engineering & structural dynamics.)
Damping modification factors (DMF) are used in modern seismic codes to adjust elastic response spectral values corresponding to 5% of viscous damping to other higher or lower damping levels. This paper presents a simple and effective procedure to estimate DMF for single-degree-of-freedom systems. Empirical expressions are proposed for displacement, velocity and acceleration response spectra, where four types of soil conditions, from hard rock to soft soil are considered. This study also examines, for the first time, the influence of artificial earthquakes on DMF. Furthermore, natural near-fault and far-fault seismic ground motions are considered where it is testified that the fault distance has no impact on DMF. Finally, it confirms that, in contrast to the considerations of many seismic codes, DMF are strongly dependent on the period of structural vibration while there are significant problems of using the same modification factor to estimate maximum displacement, velocity and seismic forces.